Virulence and antimicrobial resistance factors in Salmonella enterica serotypes isolated from pigs and chickens in central Chile - Retamal, Patricio; Gaspar, Joaquim; Benavides, María Belén; Saenz, Leonardo; Galarce, Nicolás; Aravena, Trinidad; Cornejo, Javiera; Lapierre, Lisette (Frontiers in Veterinary Science, 2022)
Salmonella enterica is a food-borne pathogen with a wide host-range that during decades has been of public health concern in developed and developing countries. In Chile, the poultry and pig industries represent the biggest contribution of meat consumption in the population, and sanitary regulations have been imposed for Salmonella control. The aim of this work was to determine and characterize Salmonella strains isolated from pigs and chicken raised on commercials farms in Chile. For this, isolates belonging to pigs (n = 46) and poultry (n = 57) were genotyped by two multiplex PCR reactions and virulotyped by the PCR detection of virulence-associated genes. In addition, isolates were serotyped and analyzed by the Kirby Bauer assay to determine their antimicrobial resistance phenotypes. From these analyses 52 genotypes, six serotypes and several multidrug resistance phenotypes and different combinations of virulence-associated genes were detected. These results suggest that S. enterica in pigs and poultry in central Chile should be monitored due to potential consequences in public and animal health.